Devide Et Impera: The United Arab Emirates’ Strategic Policy In Yemen - Ramadhan, Riskiansyah; Rohman, Syaiful; Hayatullah, Imam Khomaeni (Journal Of Middle East and Islamic Studies, 2021)
The United Arab Emirates (UAE) may have withdrawn its troops from Yemen, but its influence remains substantial and significant. From the first stage of the war, Saudi Arabia focused on the north of Yemen, while the UAE actively engaged in the north's south and coastal areas. Not only trains fighters, but the UAE also provides them with financial and political support. This is a descriptive-analytical article, using qualitative methods with data and works of literature, collected various books, journals, and online resources related to the topic. Furthermore, the author uses the "devide et impera" theory to elaborate, examine, and investigate the UAE's policy, as well as its strategy, in Yemen. This article found that UAE's divide and rule strategy is applied to achieve several interests in Yemen, such as countering terrorism, extremism, and Houthi. Nevertheless, the UAE is also ambitious to dispel al-Islah, a group affiliated to the Islamic Brotherhood.